The Issues of Wa'ad IMBT in The Fatwa DSN MUI Based on Fiqhiyyah Rules - Rahman, Muh Fudhail; Luhur, Mujhid Budi (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2021)
Abstract. This study discusses the concept and function of wa'ad in the DSN-MUI Fatwa No.85/DSN-MUI/XII/2012 concerning Wa'ad in Islamic Financial and Business Transactions, changing the contract from non-binding to binding nature. This study aims to analyze wa'ad law in IMBT in terms of its risks and benefits. This study uses data from the DSN-MUI Fatwa, Islamic jurisprudence, and other scientific papers. This study finds out that IMBT combines an ijarah contract (lease) with a sale-purchase contract or a grant. The ijarah contract, the sale, and the purchase contract are linked with an agreement. In principle, the legal status of fulfilling wa'ad in Islamic finance and business transactions is binding because it will provide benefits for the Islamic economic community, and there will be no financing problems. In the DSN-MUI fatwa, the concept of